A New Flea Species of the Genus Palaeopsylla (Insecta: Siphonaptera: Ctenophthalmidae) From Turkey. Issue 1 (25th September 2019) - Keskin, Adem
Abstract: A new flea (Insecta: Siphonaptera) species belonging to the Palaeopsylla minor -group, Palaeopsylla ( Palaeopsylla ) beaucournui n. sp. is described and illustrated. Specimens (14 males and seven females) of this new species were collected from Talpa levantis Thomas (Mammalia: Talpidae) in the deciduous mixed forest in Bursa province of Marmara Region, Turkey.